The Relation between the Sociocultural Attitudes Towards Appearance and the Lifestyle and Self-Esteem of Adolescents - Rasa Mickūnienė; Simona Pajaujienė; Rasa Jankauskienė (Lithuanian Sports University, 2018)
Background. The adolescents seeking to conform to the ideal appearance associate the reduction of weight with smoking and alcohol consumption (Haley, Hedberg, & Leman, 2010) or go on a diet instead of increasing their physical activity (Liechty, 2010). The adolescents dissatisfied with their body have lower self-esteem (Neumark- Sztainer  et  al.,  2006).  In  this  study  we  assumed  that  the  sociocultural  attitudes  towards  appearance  would  be associated  with  adolescents'  harmful  lifestyle  and  lower  self-esteem.  Research  aim  was  to  disclose  the  relation between the sociocultural attitudes towards appearance of adolescents and their lifestyle and self-esteem. Methods. The research was carried out in Kaunas schools (n = 16) using the method of written survey. In total, 805 adolescents were surveyed, 329 (41.1%) out of them were boys. The mean age (SD) of the respondents was   17.23  (0.6)  years.  Instruments:  Sociocultural  Attitudes  Towards  Appearance  Questionnaire-3  SATAQ-3-L (Thompson, van den Berg, Roehrig, Guarda, & Heinberg,  2004), Rosenberg Self-Esteem Questionnaire (Rosenberg, 1989). Physical activity (PA) was determined using the questions from the international study Health Behaviour in School-Aged Children. The frequency of dieting and having harmful habits were determined by individual questions. Results. The weight of the majority of adolescents (75.5%) was normal. The numbers of adolescents were as follows: those who smoked (39.8%), consumed alcohol (80.5%), were on diet (36.8%), and had low levels of physical activity (74.4%). The adolescents who smoked, consumed alcohol and were on diet had significantly higher scores  in  all  SATAQ  subscales.  Physically  active  adolescents  were  more  striving  to  meet  the  Internalization  of athletic body image. In the groups of boys and girls, BMI was related to more frequent sociocultural pressures   (p < .01) and more frequent dieting (p < .01). In the group of boys, the frequency of smoking was related to lower self-esteem (p < .05). In the group of girls, sociocultural pressures were related to lower self-esteem (p < .05). Conclusion. The sociocultural attitudes towards appearance of adolescents are related to more harmful lifestyle and lower self-esteem. Therefore, health literacy of the adolescents has to be increased by teaching proper attitudes towards their bodies, appropriate diet, and exercising. Keywords: sociocultural attitudes towards appearance, body image, lifestyle, physical activity, self-esteem.